Microbiology of diabetic foot infections in a teaching hospital in Malaysia: a retrospective study of 194 cases - Raja, N.S. (2007)
Diabetes mellitus is a progressive disease with chronic complications. Foot infections are a major complication of diabetes and eventually lead to development of gangrene and lower extremity amputation. The microbiological characteristics of diabetic foot infections have not been extensively studied in Malaysia. This study investigated the microbiology of diabetic foot infections and their resistance to antibiotics in patients with diabetic foot infections treated at University of Malaya Medical Centre in Kuala Lumpur, Malaysia. A retrospective analysis was conducted of clinical specimens taken from patients with diabetic foot infections over a 12-month period from July 1, 2004 to June 30, 2005. A total of 194 patients with positive clinical specimens were identified. The clinical specimens were cultured using standard aerobic and anaerobic microbiological techniques. Antibiotic sensitivity testing to different antimicrobial agents was carried out using the disk diffusion method. A total of 287 pathogens were isolated from 194 patients, an average of 1.47 organisms per lesion. The most frequently isolated pathogens were Gram-negative bacteria (52%), including Proteus spp. (28%), Pseudomonas aeruginosa (25%), Klebsiella pneumoniae (15%) and Escherichia coli (9%). Gram-positive bacteria accounted for 45% of all bacterial isolates. Staphylococcus aureus was predominant (44%) among Gram-positive bacteria, followed by Group B streptococci (25%) and Enterococcus spp. (9%). Antimicrobial susceptibility results showed that Gram-negative bacterial isolates were sensitive to imipenem and amikacin while vancomycin showed good activity against Gram-positive bacteria. The antibiogram results of this study suggest that pathogens remain sensitive to a number of widely used agents. Imipenem was equally effective against Gram-negative bacilli and Gram-positive cocci.